Opinion of Early Childhood Development Coordinators Regarding Importance of Nutrition for Cognitive Development of Young Children at ECD Level (Journal of Asian Development Studies, 2023)
It is important to elevate when it comes to kid growth; it is an important factor to consider. The study focused on the "opinion of ECD coordinators and pediatricians regarding the importance of food and nutrition for the cognitive development of young children at the ECD level. Similarly, the main question was: what are the perceptions of ECD coordinators and pediatricians regarding the role of food and nutrition on the cognitive development of young children? Food and nutrition are essential elements of human growth and developmental process? The methodology used to study the opinion of ECD coordinators and ECD pediatricians regarding the importance of food and nutrition for the cognitive development of young children was qualitative, where all the data was collected through interview protocol. Both ECD coordinators and pediatricians carried out the data. As a result of data analysis, the study has generated several findings associated with the importance of food and nutrition for the cognitive growth of young children at the ECD level. It has been found that developmental age children need proper food and nutrition for holistic development of young children. The researchers also added that ignorance of proper food and nutrition at an early age may lead to mental laziness. Proper nutrition affects students' learning; students who are taught proper nutrition can perform well in their studies and be able to make decisions, effectively concentrate, and focus on different things. On the other hand, children who are not given proper nutrition show little interest in their studies, in decision-making, and in concentrating on anything. However, parents, administrators, and ECD coordinators can overcome nutrition-related issues in studies by providing them with good nutrition at school and home. Based on the findings, the recommended to ECD coordinators that they must ensure food related to cognitive development in their lunch plan, and they must encourage homemade lunch in their schools.